MODEL PELATIHAN KEWIRAUSAHAAN BERBASIS PENERAPAN TEKNOLOGI TENUN IKAT - -, Trimurti (Universitas Slamet Riyadi, 2008)
Abstract This research is aimed to produce a model and module product of technology based entrepreneurship training on woven fabric used to improve traditional woven craftsmen businees performance, which are in decreasing condition. As the sample of this research, there are 30 traditional woven craftsmen in Jambakan Village, Bayat, Klaten Central Java, taken with purposive non random sampling method. The data collection is using questionnaire, observation and interview methods. Using descriptive qualitative data analysis and small businees entreprizing concept, it significantly knows the training need requirement for traditional woven craftsmen in enterpreneurship, technical skill and business management based mastering fields. To evaluate the product effectiveness in more functional direction to broader society, it’ll be necessary in futher research to be adopted, therefore this research is longitudinal in nature. Keywords : entrepreneurship training, traditional woven craftsmen, businees performance